Predicting osteoporosis medication receipt in Veterans with a spinal cord injury: A retrospective cohort study. (2nd November 2019) - Weaver, Frances M.; Le, Brian; Ray, Cara; Miskevics, Scott; Gonzalez, Beverly; Carbone, Laura D.
Abstract : Objective: To describe frequency and predictors of use of pharmacological therapies for osteoporosis in persons with a spinal cord injury (SCI). Design : Retrospective cohort study. Setting: United States Veterans Health Administration (VA) national databases. Participants: 11, 048 persons with a traumatic SCI who received VA health care between Fiscal Years (FY) 2005–2015. Pharmacy data from VA's Corporate Data Warehouse were used to identify prescriptions for Food and Drug Administration-approved pharmacological treatments for osteoporosis including bisphosphonates, calcitonin, denosumab, raloxifene and teriparatide. Outcome Measures: Demographics, clinical and SCI-related characteristics, receipt of a dual energy x-ray absorptiometry (DXA), and prevalent lower extremity fractures were examined to determine factors related to receiving a pharmacological agent for osteoporosis. Results: 1, 041 persons (9.4%) had a prescription for a pharmacological agent for osteoporosis; the majority ( n  = 964, 93.0%) were bisphosphonates. There was a significant decline in the number of these prescriptions from FY 2005 (13.0%) to FY 2015 (2.2%). In multivariable analysis, age (>50 years) (OR = 1.60, 95% CI 1.31–1.94); female sex (OR = 4.09, 95% CI 2.74–6.09); opioid (OR = 1.24, 95% CI 1.01–1.51) or corticosteroid (OR = 1.92, 95% CI 1.01–1.51) prescriptions; complete injury (OR = 1.26, 95% CI 1.04–1.53); receipt of a DXA scan (OR = 84.03, 95% CI 59.80–118.07) and prevalent fracture (OR = 5.43, 95% CI 4.13–7.15) were positive predictors. Black race (OR = 0.43, 95% CI 0.33–0.57) and obese BMI (OR = 0.59, 95% CI 0.45–0.76) were negative predictors. Conclusions: Prescriptions for osteoporosis medications for persons with a SCI declined in recent years. The strongest predictors for having filled these prescriptions were having had a DXA or a prevalent fracture.